ANÁLISIS SOBRE LA OFERTA DE PRODUCTOS NUTRICIONALES EN LOS BARES ESCOLARES DE CENTROS EDUCATIVOS DE LA CIUDAD DE GUAYAQUIL - Intriago Olives, Laura (2014)
The food service chain in private schools of Guayaquil is offering a lot of products with a high percentage of fat and colorants and is the main reason why obesity has increased in adolescents. The most affected ones are between six and eleven years old that are attending primary school. This issue represents the school’s responsibilities they have these days in to offer healthy light products that can benefit students in their development and growth, but there is always the fear of developing a new product that could be a failure or have negative results like low sales could make it impossible to change this routine. However there are nutritional menus that can be offered without diminishing, sales due to the lack of information and as a result they will obtain a broad consumer target with high sales, and also provide an added value that improves costumer health.